Post-Election Climate Policy in Germany: Towards a New Green Industrial Policy - Barbara Praetorius; Wolfgang Dierker (Wirtschaftsdienst)
Abstract In early 2022, the new German government presented an ambitious mitigation strategy to meet its climate protection targets. In it, industry plays a central role in two respects: in achieving emission reductions in its own production, while also generating climate-neutral products and emission-free production processes. Reconciling climate protection and competitiveness is a precondition for the success of such programme. Based on a review of previous policies, we argue for a “new green industrial policy”, involving a more pronounced government commitment to target-oriented measures and a systemic perspective on the industrial transformation process.